The mechanics of horizontal alignment in front crawl swimming reexamined - Yanai, T. (2001)
The purpose of this study was to reexamine the mechanics of horizontal alignment of front crawl swimmers on the basis of quantified rotational effect of buoyancy (buoyant torque). Three-dimensional videography was used to measure the position and orientation of the body segments of three competitive swimmers performing front crawl stroke at a sub-maximum sprinting speed. The dimensions of each body segment were defined mathematically to match the body segment parameters (mass, density, and centroid position) reported in the literature. The buoyant force and torque were computed for every video-field (60 fields/s), assuming that the water surface followed a sine curve along the length of the swimmer. The body segment model accurately represented the bodies of the swimmers (volume of the body within 0.9 % error & moment arm of buoyant force about CM within 0.1 % error). The average buoyant torque acting over the stroke cycle (mean = 22 Nm) was directed to raise the legs and lower the head. This finding contradicts the prevailing speculation that the buoyancy causes only the legs to sink throughout stroke cycle and jeopardizes the widely-accepted theoretical link between swimmer's tendency of sinking the legs in still water and the physiological cost of swimming. On the basis of a theoretical analysis of this result, it is postulated that the buoyant torque, and perhaps the forces generated by kicks, function to counteract the torque generated by the hydrodynamic forces acting on the hands, so as to maintain the horizontal alignment of the body in front crawl.